NOTES ON THE MOLLUSCAN FAUNA OF PULAU PARI - Subagjo Soemodihardjo (BERITA BIOLOGI, 1974)
Among the soores of islands that make up "Pulau Seribu",Pulau Pari is ecologically interesting. It is composed of five small islands united by a common., distantly located, outer reef.Collectively they offer a long beach line easily within our reach.The vast intertidal area, the uneven bottom topography and the nature of the bottom, give rise to different kind of habitats from which we may expect different biotic populations.